Fig. 3 in Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract - Mecca, Silvia; Casoli, Edoardo; Ardizzone, Giandomenico; Gambi, Maria Cristina (Zenodo, 2020)
Fig. 3: Percentage of leaves showing different types of leaf apex erosion (intact, mechanical, and biological) over time at the studied stations. At least 30 of the oldest leaves were examined at each month and station. Published as part of Mecca, Silvia, Casoli, Edoardo, Ardizzone, Giandomenico & Gambi, Maria Cristina, 2020, Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract, pp. 70-83 in Mediterranean Marine Science 21 (1) on page 75, DOI:10.12681/mms.20795, http://zenodo.org/record/12551640